Disabled information users in libraries: an analysis of scientific production in Librarianship and Information Science - Pinheiro Wellichan, Danielle Silva [UNESP]; Manzini, Eduardo Jose [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2021)
Users with disabilities are still unknown and pose important challenges for library practice. Therefore, analyzing the existence of this user in the context of information is a necessity to rethink the relevance of our information environments. Thus, in order to analyze how the person with disabilities, as a user of information, was approached by the literature in the area in the period from the 1970s to 2019, we sought to carry out a bibliographic survey in a database in the area of Science Information. Specific descriptors were used and the results were analyzed and categorized considering variables such as studies aimed at: 1) accessibility and inclusion; 2) Assistive Technology in libraries; 3) deficiencies more and less addressed; 4) aspects regarding professional performance; 5) inclusive practices existing in libraries. Although the literature presents significant studies and that the libraries mostly have Assistive Technology resources, the area requires attention, reflection and action in view of the real needs of a user with a disability, for a more meaningful performance that provides, from the ideal inclusion, a possible reality in the informational environment.
Keywords: Information user; Disabled people; Assistive Technology; Accessibility; Libraries